STRATEGI PENGEMBANGAN PRODUK KERUPUK KEMPLANG DENGAN METODE SWOT DI UMKM DUA PUTRI BUMI WARAS KOTA BANDAR LAMPUNG - Peri Daya Pratama; Burhan Nudin (Industrika : Jurnal Ilmiah Teknik Industri, 2021)
Abstract The strategy of developing kemplang cracker products in Dua Putri UMKM  sub-district of Bumi Waras, Bandar Lampung city is experiencing a high level of competition, the aim of this research is to produce a strategy that is in accordance with the conditions of the Dua Putri UMKM in developing a business, and to provide strategic input from the results of the research. Data collection techniques in this study were carried out by observation, interviews and questionnaires then analysed by SWOT. It is known that the IFAS value is 3,36080 with a strength factor having a value of 2.51632 and a weakness of 0.84448 with a difference in value (+) of 1.67184. and the EFAS value is 2.82229 with the opportunity factor having a value of 2.30108 and the threat factor 0.52121 with the difference in value (+) 1.77987. This value indicates that the organization is experiencing a period of growth both in sales, taste, and price differences. UMKM two putri kemplang crackers are on average in her quest to pursue a strategy of exploiting strengths to overcome weaknesses. From the results of the Cartecius diagram, that kemplang cracker Dua Putri UMKM are in quadrant 1 (one), namely an aggressive strategy, where this UMKM is in a very favorable position, this UMKM has the opportunity and strength so that it can take advantage of the existing opportunities